PEMBELAJARAN KOOPERATIF - Isti Fatonah (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2015)
Cooperative learning is successful learning strategy in which a small group, along with students from any different abilities, uses a variety of learning activities to improve their understanding of a subject. Every member of group is responsible not only to learn what has been taught but also to help others learn, in order to create an atmosphere of achievement together. Students work through assignment until successfully understand and complete it. By cooperative learning, there will be drills for students’ socialization ability to be developed and students’ relationships to be added in order to pursue their success. The big number of friends does not make students stress easily because students can tell a story freely. Socializing is essentially a process of adjusting themselves to the environment of social life.